2022
DOI: 10.1002/epi4.12575
|View full text |Cite
|
Sign up to set email alerts
|

PROVE: Retrospective, non‐interventional, Phase IV study of perampanel in real‐world clinical care of patients with epilepsy

Abstract: Objective To assess retention, dosing, efficacy, and safety of perampanel in a large cohort of patients with epilepsy during routine clinical care. Methods PROVE was a retrospective, non‐interventional Phase IV study (NCT03208660). Data were obtained retrospectively from the medical records of patients in the United States initiating perampanel after January 1, 2014, according to treating clinicians' recommendation. Retention rate was the primary efficacy endpoint. Secondary efficacy endpoints included median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 22 publications
8
20
1
Order By: Relevance
“…In addition, these data suggest that daily oral doses of perampanel are generally well tolerated in preadolescent and adolescent patients, and TEAEs reported in these populations were generally consistent with the known safety profile of perampanel, 1,2,10 as well as those reported in the overall PROVE Study population, 16,17 and resolved after treatment discontinuation. TEAEs related to hostility and/or aggression have been previously reported in patients treated with perampanel.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, these data suggest that daily oral doses of perampanel are generally well tolerated in preadolescent and adolescent patients, and TEAEs reported in these populations were generally consistent with the known safety profile of perampanel, 1,2,10 as well as those reported in the overall PROVE Study population, 16,17 and resolved after treatment discontinuation. TEAEs related to hostility and/or aggression have been previously reported in patients treated with perampanel.…”
Section: Discussionsupporting
confidence: 76%
“…However, the most common modal daily doses were similar across analyses. 16,17 It should be noted that doses used in this analysis are lower than the maximum approved dose (12 mg/d), suggesting that some preadolescent and adolescent patients benefit from treatment with the lower perampanel doses without the need for further titration up to the maximum allowed perampanel doses. In this real-world population, the most common titration schedules listed for both preadolescent and adolescent patients were 'other' (i.e., not weekly/biweekly/ every 3 weeks), followed by biweekly, and then weekly.…”
Section: Discussionmentioning
confidence: 98%
“…Our results support the findings of previous studies ( 25 , 26 ), indicating that the efficacy and safety of PER remain consistent, regardless of the baseline use of EIASMs. However, patients who are prescribed EIASMs usually need a higher dose of PER than those who are not prescribed EIASMs, to achieve an effective treatment outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, a real-life experience demonstrated that PER monotherapy seems effective and well tolerated in 20 patients, aged between 8 and 10, with childhood absence seizures ( Operto et al, 2020b ; Operto et al, 2022 ). Furthermore, clinical experience with PER monotherapy has mainly been addressed in adult patients ( Yamamoto et al, 2020 ; Chinvarun, 2022 ; Wechsler et al, 2022 ). Efficacy in adults can be extrapolated to children aged 4 years and older.…”
Section: Introductionmentioning
confidence: 99%